Backbone phylogeny and adaptive evolution of Pleurospermum s. l.: New insights from phylogenomic analyses of complete plastome data - Peng, Chang; Guo, Xian-Lin; Zhou, Song-Dong; He, Xing-Jin (Frontiers in Plant Science, 2023)
Pleurospermum is a taxonomically challenging taxon of Apiaceae, as its circumscription and composition remain controversial for morphological similarities with several related genera, leading to dispute between Pleurospermum in broad sense and strict sense. While evidence from previous molecular studies recognized plural branching lineages within the Pleurospermum s. l., it didn’t support the latest delimitation of Pleurospermum s. str. by only two closely related northern species. So far, no proper delimitation for Pleurospermum has come up, and many of the plural taxa in Pleurospermum s. l. remain unresolved, which may due to poor phylogenetic resolution yielded barely from ITS sequences. Herein, we newly assembled 40 complete plastome from 36 species of Pleurospermum s. l. and related genera, 34 of which are firstly reported, and generated a well-resolved backbone phylogeny in a framework of subfamily Apioideae. From the phylogeny with greatly improved resolution, a total of six well-supported monophyletic lineages within Pleurospermum s. l. were recognized falling in different major clades of Apioideae. Combining morphological characters with phylogenetic inference, we suggested to re-delimit the Pleurospermum s. str. by introducing 9 species mainly from Himalayan regions and proposed its boundary features; the remaining species were suggested to be exclude from Pleurospermum to incorporated into their more related taxa revealed. On this basis, plastome comparison revealed the highly conservatism but also mild differences among lineages in plastome structure and gene evolution. Overall, our study provided a backbone phylogeny essential for further studies to the taxonomically difficult taxa within Pleurospermum s. l..